Selective corticofugal modulation on sound processing in auditory thalamus of awake marmosets. (18th July 2022) - Wang, Xiaohui; Zhang, Yuanqing; Zhu, Lin; Bai, Siyi; Li, Rui; Sun, Hao; Qi, Runze; Cai, Ruolan; Li, Min; Jia, Guoqiang; Cao, Xinyuan; Schriver, Kenneth E; et al.
Abstract: Cortical feedback has long been considered crucial for the modulation of sensory perception and recognition. However, previous studies have shown varying modulatory effects of the primary auditory cortex (A1) on the auditory response of subcortical neurons, which complicate interpretations regarding the function of A1 in sound perception and recognition. This has been further complicated by studies conducted under different brain states. In the current study, we used cryo-inactivation in A1 to examine the role of corticothalamic feedback on medial geniculate body (MGB) neurons in awake marmosets. The primary effects of A1 inactivation were a frequency-specific decrease in the auditory response of most MGB neurons coupled with an increased spontaneous firing rate, which together resulted in a decrease in the signal-to-noise ratio. In addition, we report for the first time that A1 robustly modulated the long-lasting sustained response of MGB neurons, which changed the frequency tuning after A1 inactivation, e.g. some neurons are sharper with corticofugal feedback and some get broader. Taken together, our results demonstrate that corticothalamic modulation in awake marmosets serves to enhance sensory processing in a manner similar to center-surround models proposed in visual and somatosensory systems, a finding which supports common principles of corticothalamic processing across sensory systems.